Clinical efficacy and biomarker analysis of dual PD-1/CTLA-4 blockade in recurrent/metastatic EBV-associated nasopharyngeal carcinoma - Lim, Darren Wan-Teck (NATURE PORTFOLIO, 2024)
10.1038/s41467-023-38407-7